FROM PERCEPTION TO ENROLLMENT: FACTORS SHAPING VOCATIONAL SCHOOL CHOICE IN KEDIRI - Damayanti; Prio Utomo (ULTIMA Management, 2026)
This study tries to analyze the factors affecting students' interest in choosing private vocational high schools in Kediri City, where severe competition in registration continues so that there is a risk of a lack of qualified human resources and sustainable improvement of regional economy. The aim of this study is to find out how educational quality, parental involvement, education costs, major/chosen study subject, and promotion influences students’ intention to register in an institution through cognitive attitudes and affective attitudes. Both the antecedents and consequences of intentions are considered through the application of its components so that it combines two constructs of attitude, namely cognitive and affective attitudes, in order to form a unique research novelty that integrates the Stimulus–Organism–Response (SOR) framework in the context of private vocational education at a regional level where this area has rarely been studied empirically before. Surveys were conducted on 127 ninth graders from a junior high school (ninth grade) and quantitative methods were used. The data were analyzed with the Structural Equation Modeling–Partial Least Squares (SEM-PLS) to validate the proposed structural relationships among variables. The results suggest that major selection and the use of developing strategies have the most influential effects on cognitive and emotional attitudes. Education costs during the enrollment phase also impact students significantly. The findings indicate that meeting students' interest with the study program, providing competitive tuition costs, and leveraging effective persuasive communication strategies for promotion would be critical to gain enrollment in vocational school.